Well-defined Co9S8 cages enable the separation of photoexcited charges to promote visible-light CO2 reduction. Issue 43 (22nd October 2021) - Lin, Xiahui; Xie, Zidong; Su, Bo; Zheng, Mei; Dai, Wenxin; Hou, Yidong; Ding, Zhengxin; Lin, Wei; Fang, Yuanxing; Wang, Sibo
Abstract : Well-defined Co9 S8 cages with high performance for boosting photo-induced charge separation and transfer are first exploited to promote visible-light CO2 reduction. Abstract : Exploring affordable cocatalysts with high performance for boosting charge separation and CO2 activation is an effective strategy to reinforce CO2 photoreduction efficiency. Herein, well-defined Co9 S8 cages are exploited as a nonprecious promoter for visible-light CO2 reduction. The Co9 S8 cages are prepared via a multistep strategy with ZIF-67 particles as the precursor and fully characterized by physicochemical techniques. The hollow Co9 S8 cocatalyst with a high surface area and profuse catalytically active centers is discovered to accelerate separation and transfer of light-induced charges, and strengthen concentration and activation of CO2 molecules. In a hybrid photosensitized system, these Co9 S8 cages efficiently promote the deoxygenative reduction of CO2 to generate CO, with a high yield rate of 35 μmol h −1 ( i.e., 35 mmol h −1 g −1 ). Besides, this cocatalyst is also of high stability for the CO2 photoreduction reaction. Density functional theory (DFT) calculations reveal that the Ru(bpy)3 2+ photosensitizer is strongly absorbed on the Co9 S8 (311) surface through forming four Co–C bonds, which can serve as the "bridges" to ensure quick electron transfer from the excited photosensitiser to the active Co9 S8 cocatalyst, thus promoting the separation of photoexcited charges for ehannced CO2 reduction performance.